Variation of Long Non-Coding RNA And mRNA Profiles in Breast Cancer Cells With Influences of Adipocytes - Cao, Xin-Hui; Yang, Kai; Liang, Ming-Xing; Ma, Pei; Xu, Di; Fei, Yin-Jiao; Zhang, Wei; Chen, Xiu; Tang, Jin-Hai (Frontiers in Oncology, 2021)
Background: It is well known that obesity is one of the risks for incurrence and development in breast cancer patients. Long non-coding RNAs(lncRNAs) are reported to participate in the composition of tumor microenvironment and to regulate breast cancer cell metabolic activities. However, there was rare study focused on the lncRNAs in breast cancer with the influences of adipocytes. The study aimed to investigate lncRNAs expression profiles and discover potential biomarkers to predict the incidence and progression of adipocyte-associated-breast cancer. Methods: We co-cultured adipocytes with breast cancer cells and profiled the expression of lncRNAs as well as mRNAs by using the RNA-sequencing method. Wound Healing, Migration assays and Invasion assays were applied to verify the invasion and metastasis of cancer cells. Results: MDA-MB-231/Hpa-V and SkBr3/Hpa-V cells showed elevated migration and invasiveness compared to the control group. A sum of 371 mRNAs (181 upregulated and 190 downregulated) and 850 lncRNAs(414 upregulated and 436 downregulated) were differentially expressed in MDA-MB-231/Hpa-V comparing to MDA-MB-231(P < 0.05; |log2 (fold change)|>1.2). GO enrichment, KEGG pathway and interaction networks demonstrated that differentially expressed lncRNAs were involved in functional categories, such as material metabolism, which might lead to the progression of breast cancer. Conclusion: Our study detected a lncRNA profile in breast cancer cells affecting by adipocytes and provided a better understanding of the tumor microenvironment. LncRNAs may be helpful to predict the therapeutic responses and prognosis of obese breast cancer patients.